An Asp49 Phospholipase A2 from Snake Venom Induces Cyclooxygenase-2 Expression and Prostaglandin E2 Production via Activation of NF-κB, p38MAPK, and PKC in Macrophages - Moreira, Vanessa (2014)
Phospholipases A2 (PLA2) are key enzymes for production of lipid mediators. We previously demonstrated that a snake venom sPLA2 named MT-III leads to prostaglandin (PG)E2 biosynthesis in macrophages by inducing the expression of cyclooxygenase-2 (COX-2). Herein, we explored the molecular mechanisms and signaling pathways leading to these MT-III-induced effects. Results demonstrated that MT-III induced activation of the transcription factor NF-κB in isolated macrophages. By using NF-κB selective inhibitors, the involvement of this factor in MT-III-induced COX-2 expression and PGE2 production was demonstrated. Moreover, MT-III-induced COX-2 protein expression and PGE2 release were attenuated by pretreatment of macrophages with SB202190, and Ly294002, and H-7-dihydro compounds, indicating the involvement of p38MAPK, PI3K, and PKC pathways, respectively. Consistent with this, MT-III triggered early phosphorylation of p38MAPK, PI3K, and PKC. Furthermore, SB202190, H-7-dihydro, but not Ly294002 treatment, abrogated activation of NF-κB induced by MT-III. Altogether, these results show for the first time that the induction of COX-2 protein expression and PGE2 release, which occur via NF-κB activation induced by the sPLA2-MT-III in macrophages, are modulated by p38MAPK and PKC, but not by PI3K signaling proteins.